Archetypal trajectories of social, psychological, and spiritual wellbeing and distress in family care givers of patients with lung cancer: secondary analysis of serial qualitative interviews. (10th June 2010) - Murray, Scott A; Kendall, Marilyn; Boyd, Kirsty; Grant, Liz; Highet, Gill; Sheikh, Aziz
Abstract : Objective To assess if family care givers of patients with lung cancer experience the patterns of social, psychological, and spiritual wellbeing and distress typical of the patient, from diagnosis to death. Design Secondary analysis of serial qualitative interviews carried out every three months for up to a year or to bereavement. Setting South east Scotland. Participants 19 patients with lung cancer and their 19 family carers, totalling 88 interviews (42 with patients and 46 with carers). Results Carers followed clear patterns of social, psychological, and spiritual wellbeing and distress that mirrored the experiences of those for whom they were caring, with some carers also experiencing deterioration in physical health that impacted on their ability to care. Psychological and spiritual distress were particularly dynamic and commonly experienced. In addition to the "Why us?" response, witnessing suffering triggered personal reflections in carers on the meaning and purpose of life. Certain key time points in the illness tended to be particularly problematic for both carers and patients: at diagnosis, at home after initial treatment, at recurrence, and during the terminal stage. Conclusions Family carers witness and share much of the illness experience of the dying patient. The multidimensional experience of distress suffered by patients with lung cancer was reflected in the suffering of their carers in the social, psychological, and spiritual domains, with psychological and spiritual distress being most pronounced. Carers may need to be supported throughout the period of illness not just in the terminal phase and during bereavement, as currently tends to be the case.